Phosphodiesterase 4 is overexpressed in keloid epidermal scars and its inhibition reduces keratinocyte fibrotic alterations - Javier Milara; Pilar Ribera; Severiano Marín; Paula Montero; Inés Roger; Julio Cortijo (BMC, 2024)
Abstract Background Epidermal remodeling and hypertrophy are hallmarks of skin fibrotic disorders, and keratinocyte to mesenchymal (EMT)-like transformations drive epidermis alteration in skin fibrosis such as keloids and hypertrophic scars (HTS). While phosphodiesterase 4 (PDE4) inhibitors have shown effectiveness in various fibrotic disorders, their role in skin fibrosis is not fully understood. This study aimed to explore the specific role of PDE4B in epidermal remodeling and hypertrophy seen in skin fibrosis. Methods In vitro experiments examined the effects of inhibiting PDE4A-D (with Roflumilast) or PDE4B (with siRNA) on TGFβ1-induced EMT differentiation and dedifferentiation in human 3D epidermis. In vivo studies investigated the impact of PDE4 inhibition on HOCl-induced skin fibrosis and epidermal hypertrophy in mice, employing both preventive and therapeutic approaches. Results The study found increased levels of PDE4B (mRNA, protein) in keloids > HTS compared to healthy epidermis, as well as in TGFβ-stimulated 3D epidermis. Keloids and HTS epidermis exhibited elevated levels of collagen Iα1, fibronectin, αSMA, N-cadherin, and NOX4 mRNA, along with decreased levels of E-cadherin and ZO-1, confirming an EMT process. Inhibition of both PDE4A-D and PDE4B prevented TGFβ1-induced Smad3 and ERK1/2 phosphorylation and mesenchymal differentiation in vitro. PDE4A-D inhibition also promoted mesenchymal dedifferentiation and reduced TGFβ1-induced ROS and keratinocyte senescence by rescuing PPM1A, a Smad3 phosphatase. In vivo, PDE4 inhibition mitigated HOCl-induced epidermal hypertrophy in mice in both preventive and therapeutic settings. Conclusions Overall, the study supports the potential of PDE4 inhibitors, particularly PDE4B, in treating skin fibrosis, including keloids and HTS, shedding light on their functional role in this condition.